The effectiveness of employer branding in attracting talented employee: Systematic literature review (Lighthouse Publishing, 2022)
Attracting and keeping the ideal employees at the moment is a challenge for businesses. For businesses to be successful, it is essential to develop tactics and implement plans of activities that will support them establish a competitive place on the industry for top experts. Employer branding is a process used by top management to establish a specificity for the job and maintain the firm's public image. Employer branding is a term where the company presents the firm's reputation and credibility where extant workers' favourable phrase of tongue promotes the recent institution to the outside world. Employer branding is crucial in persuading talented people to apply to the company. The goal of this Systematic Literature Review is to examine employer branding's effectiveness in luring potential employees in greater detail as well as the aspects that contribute to its development. The result of this research is that despite the fact that each company had a distinctive branding strategy, job applicants were not actually aware of it. Instead of the strategic branding image that firms are working to create and promote, potential applicants seem to be drawn to businesses based on their past interactions with them and the perceptions of them that already exist in the community. This shows that in order to continue luring in the top candidates, these businesses must be more watchful and worried about influencing staff thoughts through effective and deliberate communication of their branding initiatives to potential employees.